One year of cooperation in health: UG/UTMB/THF projects (Univ. of Guyana. Faculty of Health Sciences [Georgetown]GY, 1992)
Reports on the collaborative activities for the improvement of community health status between the Faculty of Health Sciences, University of Guyana, the University of Texas Medical Branch at Galveston and the Health Foundation in New York. Provides individual project reports, projections for future cooperation and reports on funding.
DC